The Complex Role of Aluminium Contamination in Nickel‐Rich Layered Oxide Cathodes for Lithium‐Ion Batteries. Issue 12 (19th November 2021) - Lee, Juhan; Amari, Houari; Bahri, Mounib; Shen, Zonghao; Xu, Chao; Ruff, Zachary; Grey, Clare P.; Ersen, Ovidiu; Aguadero, Ainara; Browning, Nigel D.; Mehdi, B. Layla
Abstract: Invited for this month's cover picture is the group of Dr B. Layla Mehdi from the University of Liverpool. The cover picture demonstrates the impact of Al impurities on the nickel‐rich NMC cathodes. This observation of increased Al content can bring new insights into the ongoing discussions concerning the capacity fading phenomenon of nickel‐rich layered oxide materials in lithium‐ion batteries. Read the full text of the Article at 10.1002/batt.202100110 . Abstract : "This work emphasizes the importance and role of Al‐based impurities in Ni‐rich NCM cathode materials, which greatly affect their phase transformation and stability…." Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding Article on 10.1002/batt.202100110 .